Association between traumatic brain injury and prison charges: a population-based cohort study. (11th May 2020) - Matheson, Flora I.; McIsaac, Kathryn E.; Fung, Kinwah; Stewart, Lynn A.; Wilton, Geoff; Keown, Leslie A.; Nathens, Avery B.; Colantonio, Angela; Moineddin, Rahim
ABSTRACT: Background: Traumatic Brain Injury (TBI) is a serious hidden health issue disproportionately affecting people who experience incarceration. Objective: We examined the association between TBI and serious disciplinary charges among men and women sentenced by the courts to terms of two or more years. Methods: The study originated in Ontario, Canada and used linked administrative health and correctional data. The cohort included adults experiencing their first federal sentence between 1998 and 2011 (N = 12, 038). We examined disciplinary charges incurred 2 years post-sentence commencement. TBI was defined using the International Classification of Diseases (ICD-9 and ICD-10) diagnostic codes. Robust Poisson regression was conducted to assess the association between TBI and disciplinary charges. Findings: The prevalence of TBI for the full sample was 13.2%. One-third of adults with a recent TBI had a serious disciplinary charge. The unadjusted risk of incurring a serious charge for those with a history of TBI was 39% higher than those with no history of TBI (CI: 1.29–1.49). The adjusted risk was 1.14 (CI: 1.06–1.22). Conclusions: TBI is a serious health concern that makes it difficult for incarcerants to adjust to prison. Additional support/resources are needed to support those with histories of TBI.